Ambient Air Pollution and Daily Hospital Admissions for Respiratory Disease in Children in Guiyang, China - Hao Zhou; Tianqi Wang; Fang Zhou; Ye Liu; Weiqing Zhao; Xike Wang; Heng Chen; Yuxia Cui (Frontiers Media S.A., 2019)
Objectives: To investigate the association between ambient air pollutant exposure and daily hospital admissions for respiratory diseases in children in Guiyang.Methods: Clinical data of pediatric inpatients with respiratory disease from 2009 to 2016 in Guizhou Provincial People's Hospital and PM2.5, NO2, PM10, and SO2 concentration data were retrieved. A canonical correlation analysis (CCA) was applied to analyse the association between air pollutants and daily hospital admissions for respiratory diseases. A reproducibility analysis was applied to analyse the association between air pollution and the duration and direct cost of hospitalization. The support vector regression (SVR) method was applied to determine whether air pollution data could predict the daily hospital admissions for the upcoming day.Results: A total of 10,876 inpatients with respiratory diseases were included between January 1, 2009 and December 31, 2016. The CCA showed significant correlations between air pollution and daily hospital admissions (r = 0.3564, p < 0.001), the duration of hospitalization (r = 0.2911, p < 0.001) and the economic cost of hospitalization (r = 0.2933, p < 0.001) for respiratory disease. PM10 contributed most to daily hospital admissions for respiratory disease; the concentration the day before hospitalization contributed most to the daily hospital admissions for respiratory disease. There was a slightly stronger correlation between air pollution and respiratory disease in children aged 2-18 years (R = 0.36 vs. R = 0.31 in those under 2 years old). No significant difference was found between male and female patients. The prediction analysis showed that air pollution could successfully predict daily pediatric inpatient hospital admissions (R = 0.378, permutation p < 0.001).Conclusions: Air pollution was significantly associated with hospital admissions, hospitalization duration and the economic cost of hospitalization in children with respiratory diseases. The maximum effect occurred on the day before hospitalization. The effect of PM10 on daily pediatric inpatient hospital admissions for respiratory disease was the greatest among the pollutants evaluated.